Changes in teaching from the perspective of novice and retired teachers: Present and past in review - García-Hernández, María Luisa; Bernárdez-Gómez, Abraham; Porto-Currás, Mónica; Torres-Soto, Ana (Frontiers in Education, 2022)
Background: This study aimed to understand the perceptions that Spanish teachers of different educational levels have about the functions attributed to them, the overload of administrative tasks that they face daily, and the external consideration that their professional profile has raised. A generational perspective was adopted in this study, taking into consideration different educational stages: Early Childhood, Primary, and Secondary Education. Methods: This descriptive study was developed using a qualitative methodology. The data were extracted through semi-structured interviews with 60 Spanish teachers from public schools. The information was analyzed with the qualitative data analysis tool ATLAS.ti, version 22. Results: The results extracted from this study expose the overload of administrative work that teachers face daily, preventing them from developing pedagogical tasks that can improve their practice. In addition, the results highlight that a series of prejudices and negative external considerations toward the figure of the teacher are developing in the society. Conclusions: It can be concluded that older and more experienced teachers in educational centers place more emphasis on the work overload that they have assumed over the years in their work. However, novice teachers do not show as much concern about this work overload. Additionally, teachers state that the society has a negative regard for their work.